Pemerolehan Bahasa Pada Anak (Kajian Literatur dalam Psikolinguistik) - Rama Rosmanti; Missriani M; Siti Rukiyah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study was conducted with the aim of describing language acquisition in children.  This study is a qualitative literature study. This study attempts to explain findings from previous research related to language acquisition in children.  Study results shows that in general language acquisition in children goes through several stages or phase.  However, not all children of the same age will experience the process  development or acquisition of a common language.  There are various factors that can do this influence the process of language acquisition in children.  These factors are sometimes is supportive so that the child's acquisition process can be faster and more frequent is inhibiting so that the process of acquiring a child tends to be delayed, both from the side phonology, semantics and syntax.  There are two main factors that have the most influence are parents and the surrounding environment.  Therefore, it is appropriate for parents and the environment  around children are able to provide positive stimuli, so that children can too provide responses in the form of positive developments as well.